Trust-based work time and the productivity effects of mobile information technologies in the workplace - Steffen Viete; Daniel Erdsiek (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
We investigate whether the returns to mobile information and communication technology (ICT) in the workplace are contingent on granting employees autonomy over the structure of their workday through trust-based work time arrangements (TBW). Our regression analysis is based on a production function framework and exploits fine-grained firm survey data on ICT use and organisational practices for 1,045 service firms in Germany. We find empirical support for the argument that the returns to mobile ICT are higher when TBW allows for discretion over when, where and how to perform work-related tasks. The finding holds when we account for more limited forms of workplace flexibility, suggesting that the high degree of formal employee autonomy under TBW drives the complementarity between mobile ICT and organisational practices.
urn:nbn:de:bsz:180-madoc-447750
Keywords: D22; L22; M10; O33; 330; mobile information and communication technologies; ICT; trust-based work time; work organisation; complementarity; productivity; firm performance